Comprehensive Biological Assessment of Rutagraveolens: Anti-inflammatory and Antioxidant Activities via In Vitro, In Vivo, and In Silico Approaches - شريط فاطمة الزهراء; سليماني شروق; قعري خلود (University of eloued . جامعة الوادي, 2025)
Abstract This study addresses the comprehensive biological evaluation of Rutagraveolens (commonly known as rue), focusing on its anti-inflammatory and antioxidant properties through a multidisciplinary approach. This includes biochemical analyses, in vitro laboratory experiments, in vivo animal testing, and in silico computational simulations. The importance of this research lies in the ongoing search for safer natural therapeutic alternatives compared to conventional drugs, which are often associated with long-term side effects. The study begins with an extensive overview of inflammation—its types, stages, and key triggering factors—highlighting the roles played by immune cells and chemical mediators. It also discusses anti-inflammatory drugs, both steroidal and non-steroidal, explaining their mechanisms of action and limitations in clinical use. Within this context, Rutagraveolensis presented as a traditional medicinal plant rich in flavonoids and essential oils. Plant samples were collected from a desert region in southeastern Algeria, and subjected to various extraction methods to obtain both aqueous extracts and essential oils. These extracts underwent advanced chemical analyses using UPLC-MS/MS and GC-MS technologies, which identified bioactive compounds such as rutin, naringin, and syringic acid in the aqueous extract, and 2-Undecanone in the essential oil. The biological activity of the extracts was assessed in vitro through protein denaturation inhibition tests to determine anti-inflammatory potential, and DPPH assays to evaluate antioxidant activity. The results demonstrated notable efficacy, particularly at higher concentrations. In addition, in silico simulations were conducted to predict the bioavailability and toxicity of the compounds, as well as their binding affinities to key enzyme targets such as COX-1 and Glutathione Reductase, supporting their anticipated anti-inflammatory mechanisms. In the in vivo component, animal models (Wistar rats) were exposed to the herbicide glyphosate and subsequently treated with the plant extracts. Hematological, biochemical, and antioxidant enzyme markers were analyzed, alongside histopathological examinations of affected tissues. The findings revealed significant improvement in both physiological and histological parameters, reinforcing the therapeutic potential of Rutagraveolens. The study concludes that Rutagraveolens possesses promising properties as a natural source of bioactive compounds with anti-inflammatory and antioxidant effects. It recommends further clinical and exploratory research to develop pharmaceutical products based on the plant’s constituents, within the framework of complementary and alternative medicine. The study concludes that Rutagraveolens possesses promising properties as a natural source of bioactive compounds with anti-inflammatory and antioxidant effects. It recommends further clinical and exploratory research to develop pharmaceutical products based on the plant’s constituents, within the framework of complementary and alternative medicine. The study concludes that Rutagraveolenspossesses promising properties as a natural source of bioactive compounds with anti-inflammatory and antioxidant effects. It recommends further clinical and exploratory research to develop pharmaceutical products based on the plant’s constituents, within the framework of complementary and alternative medicine.
بيولوجباوفزيولوجيا النبات
Keywords: Comprehensive Biological Assessment of Rutagraveolens: Anti-inflammatory and Antioxidant Activities via In Vitro; In Vivo; and In Silico Approaches